Marginal Cost Pricing of Recursive Lumpy Investments - Starrett, David A. (Review of Economic Studies, 1978)
Journal Article Marginal Cost Pricing of Recursive Lumpy Investments Get access David A. Starrett David A. Starrett Stanford University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 2, June 1978, Pages 215–227, https://doi.org/10.2307/2297336 Published: 01 June 1978 Article history Received: 01 November 1975 Accepted: 01 January 1977 Published: 01 June 1978